Influence of Mn content on the intrinsic energy barriers of paramagnetic FeMn alloys from longitudinal spin fluctuation theory - Dong, Zhihua; Schönecker, Stephan; Chen, Dengfu; Li, Wei; Lu, Song; Vitos, Levente (International journal of plasticity, 2019)
First-principles calculations were performed to investigate the influence of Mn content on the intrinsic energy barriers (IEBs) of paramagnetic FeMn alloys with face-centered cubic (fcc) structure. The IEBs were derived from the free energies accounting for longitudinal spin fluctuations (LSFs). LSFs are demonstrated to be important for the quantitative description of IEBs and their alloying dependencies at finite temperature. The unstable stacking and unstable twinning fault energies of the fcc phase slightly decrease with Mn content, whereas the intrinsic stacking fault energy (γisffcc) is predicted to monotonically increase. This latter finding contradicts the experimentally reported, local minimum of γisf in the fcc/hexagonal close-packed (hcp) coexistence region. The partitioning of Mn during the fcc/hcp phase transition is proposed to reconcile theory and experiment. Both temperature and impurities ([C] and Cr) hardly influence the monotonic concentration dependence of γisffcc but considerably alter the magnitude. The fcc/hcp interfacial energy is nearly independent of Mn concentration in contrast to the parabolic dependence predicted in thermodynamic modeling. In contrast to the fcc phase, the estimated intrinsic stacking fault energy of the ideal hcp structure monotonically decreases with Mn content and temperature. A high twinnability is predicted at 450 K within the stability field of the paramagnetic fcc FeMn alloys. •γisf, γusf, and γutf of paramagnetic FeMn binaries are predicted as a function of Mn concentration at finite temperature, explicitly accounting for longitudinal spin fluctuations.•γisf of paramagnetic fcc FeMn is predicted to monotonically increase with Mn, in contrast to a local minimum reported experimentally.•Longitudinal spin fluctuations are demonstrated to be important for the adequate description of the intrinsic energy barriers and their concentration dependencies in Fe-Mn system.